2023
DOI: 10.3389/fphys.2022.1081881
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cells in intimal hyperplasia, an update

Abstract: Arterial occlusive disease is the leading cause of death in Western countries. Core contemporary therapies for this disease include angioplasties, stents, endarterectomies and bypass surgery. However, these treatments suffer from high failure rates due to re-occlusive vascular wall adaptations and restenosis. Restenosis following vascular surgery is largely due to intimal hyperplasia. Intimal hyperplasia develops in response to vessel injury, leading to inflammation, vascular smooth muscle cells dedifferentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 290 publications
1
28
0
Order By: Relevance
“…TSP‐2, which is primarily produced by SMC and fibroblasts, has been described to be an important modulator of cell‐matrix interactions and regulator of SMC and EC proliferation 27,36 . TSP‐2 role in increasing SMC proliferation, a key step in the formation of IH, has been clearly described 37,38 . Our study suggested that the downregulation of TSP‐2 inhibits this dysregulated proliferation of cells, as demonstrated by the decrease of Ki‐67 in CCA treated with CLICK‐gelatin + TSP‐2 siRNA.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…TSP‐2, which is primarily produced by SMC and fibroblasts, has been described to be an important modulator of cell‐matrix interactions and regulator of SMC and EC proliferation 27,36 . TSP‐2 role in increasing SMC proliferation, a key step in the formation of IH, has been clearly described 37,38 . Our study suggested that the downregulation of TSP‐2 inhibits this dysregulated proliferation of cells, as demonstrated by the decrease of Ki‐67 in CCA treated with CLICK‐gelatin + TSP‐2 siRNA.…”
Section: Discussionsupporting
confidence: 55%
“…27,36 TSP-2 role in increasing SMC proliferation, a key step in the formation of IH, has been clearly described. 37,38 Our study suggested that the downregulation of TSP-2 inhibits this dysregulated proliferation of cells, as demonstrated by the decrease of Ki-67 in CCA treated with CLICK-gelatin + TSP-2 siRNA. Further supporting inhibition of cell proliferation as an important mechanism of TSP-2 downregulation in attenuating IH formation.…”
Section: Discussionmentioning
confidence: 63%
“…Importantly, migration of fibroblasts to the intima plays a well-documented role in the development of intimal hyperplasia and atherosclerosis. 59 Within the intima of distended veins, myeloid cells are also enriched, further underscoring the recruitment and infiltration of immune cells initiated by the effects of distension on the endothelium. Lastly, SMCs display increased enrichment in the adventitia of distended veins, supporting our hypothesis that while the overall proportion of SMCs decreases following distension, SMCs present in the distended veins may undergo VSMC-reprogramming toward a synthetic phenotype facilitating their migration to the adventitia.…”
Section: Resultsmentioning
confidence: 98%
“…This is due to their composition, which includes polymer cores and lipid/lipid‐PEG shells (Hadinoto et al, 2013) (Figure 3d). Intimal hyperplasia and a high level of lipid and platelet adhesion following localized injury caused by the stent can be counteracted by a prohealing, noncytotoxic remodeling approach for the repression of SMC lipid uptake and hyperproliferation, which could be effective in preventing further oxidative stress, SMC proliferation, and platelet adhesion within stented arteries (Chan et al, 2016; Déglise et al, 2022). Chan et al reported that the lipid hybrid NP‐based therapy causes effective vascular targeting and controlled drug release.…”
Section: Stents Coated With Nanoparticle‐based Therapeuticsmentioning
confidence: 99%